Pengaruh Konservatisme Akuntansi, Kepemilikan Institusi dan Asing terhadap Kualitas Laba dengan Variabel Moderasi Manajemen Laba - Adri Putra Nugraha; Reyhan Achmad Karis; Rizka Fitriasari (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
This descriptive quantitative study aims to examine the effects of accounting conservatism, institutional ownership, and foreign ownership on the earnings quality of manufacturing companies. From the population of manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period, 51 companies were selected as samples through purposive sampling. The results of multiple linear regression analysis show that accounting conservatism and institutional ownership have positive effects on earnings quality, and earnings management strengthens the effect of institutional ownership on earnings quality. However, this study does not find any positive effect of foreign ownership on earnings quality, nor evidence that earnings management strengthens the effect of foreign ownership on earnings quality. Based on these findings, this study suggests that manufacturing companies consider applying the principle of accounting conservatism to improve earnings quality.